A Method for the Coefficient Superposition Buckling Bearing Capacity of Thin-Walled Members - Bing Xu; Lang Wang; Qin Liu; Rui Wang; Bing Kong; Bo Xu (Buildings, 2024)
Axial compression tests were conducted on short rhombic tubes of different cross-sectional shapes. The deformation modes of the rhombic short tubes were obtained. To induce a finite element model with deformation modes consistent with the actual working conditions, buckling modes are introduced into the model as the initial imperfections of the structure. However, the buckling modes resulting from finite element buckling analyses often do not meet the needs of actual crushing modes. A coefficient superposition method of solution is proposed to derive modal characteristics consistent with the actual deformation modes by linear superposition of the buckling modes. Through the study of three aspects of theory, test, and simulation, and the comparison and verification of this method with the simulation results of related literature, the results show that the indexes derived from this method are closer to the actual circumstances and are more expandable, which provides a reference for the project.